Towards an Inclusive Village: Literacy and Education for People with Disabilities Through the Development of Grape Planting Techniques (Vitis Vinifera L) Taman Ayu Village - Herdiana, Herdiana; Andiana, Baiq Dewi Lita; Mappanganro, Nurlailah (Unram Journal of Community Service, 2024)
People with disabilities are identical to people who are disabled, weak, stupid and backward. People with disabilities are no longer seen as problematic people, by providing equal access and being inclusive for everyone in their society (168 169). Equal roles for people with disabilities are an important issue for the government. Recognition of equal rights for groups with disabilities, both in terms of education, employment opportunities and others. Community service activities carried out by Herdiana, et al. in Taman Ayu village, in 2023 became the main basis for empowering people with disabilities and knowledge for people with disabilities, especially in the equality garden by involving groups with disabilities. Taman Ayu Village, Gerung District, West Lombok Regency, West Nusa Tenggara (NTB) in the "Equality Garden" group consisting of 15 people consisting of people with hearing and speech impairments which was carried out in June-December 2024 with the community service implementation team being a collaboration of 3 fields of science, namely agribusiness, accounting and agroecotechnology and involving 3 students from different study programs (fields of science). The purpose of this activity is to provide literacy and education about grape cultivation techniques, improve grape cultivation technique skills, financial management in business through ongoing training and mentoring. The forms of activities include literacy counseling and education for people with disabilities in grape cultivation techniques (Vitis Vinifera L), business management training and financial recording management, mentoring and coaching in marketing using digital marketing (marketplace: Facebook, Shopie, Tokopedia) and mentoring in submitting business legality. The hope of this activity is that groups with disabilities have skills in the field of grape cultivation, skills in management and financial recording of businesses so that from this activity a new business can be formed so that the goal of this activity is the independence of the disabled group's business. Collaboration between the service team (academics) and the village in the form of ongoing mentoring and coaching will be carried out until they have an independent business